ASONANSI DAN ALITERASI NOVEL SAFIR CINTA: DWILOGI PEREMPUAN MENITI CAHAYA KARYA FARADINA IZDHIHARY: KAJIAN STILISTIKA - Fitriyah, Husniyatul (Jurnal Sastra Aksara, 2018)
Stylistics knowledge are shape knowledge objective, because observation from target knowledge and explanation. Stylistics knowledge are knowledge which focus on shape utilizing signal system in literature creation who got by rational empirical who able to responsibility. The base of empirical are refer to appropriate base of conceptual with way work who use if connected with characteristic fact who become target knowledge. At literature appreciation, knowledge stylistic analysis purpose for deeply enjoyable facilitate, comprehend, and inspire symbol system in literature creation, to know phrase expressive by writer. This thorough formulate problem that is, sound language employing in novel Safir Cinta: Dwilogi Perempuan Meniti Cahaya by Faradina Izdhihary Stylistics knowledge with descriptive-qualitative. The result to conclude of the conformity story in condition of the meaning languge.